SEMANTIC ROLES â€œAGENTâ€ AND â€œAFFECTEDâ€ IN TRILINGUAL BALINESE FOLKLORES: A STUDY OF SEMANTICS - Iskandar, Anwar; Sari, Retno Purwani (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2020)
The research proposes that entities occupying as AGENT and AFFECTED apparently appear in clauses of trilingual Balinese Folklores. Although they play as main roles in semantic role system, a concept of animate things has a potential influence in giving a notion. Thus, the aims of the research are to identify and to analyze: (1) the roles of entities in semantic role system, and (2) a concept of animate things. Applying research procedures of analytic descriptive method, collected and classified data are analyzed using Kreidlerâ€™s semantic role theory (1998). Briefly, Kreidler (1998:70) claims that AGENT is an entity or a main actor in an event that results or gives a change to another entity, and AFFECTED is an entity that receives the change. In this research, 48 data from 9 books of trilingual Balinese Folklores are analyzed based on the issues suggested. As a result, 45 AGENTS and 49 AFFECTED are identified. Furthermore, all those roles take animate things.